Existence and Effectiveness of Alternative Institutions of Dispute Resolution of Indonesian Banking (LAPSPI) in the Implementation of Mediation - Nurviviani; Pujiyono (International Journal of Asian Social Science, 2019)
Alternative Institution of Dispute Resolution of Indonesian Banking (LAPSPI) is an institution created to facilitate the resolution of banking disputes. LAPSPI is present and needed along with the increasing economic development in Indonesia. Therefore the writer wants to know the existence and effectiveness of the Alternative Institution of Dispute Resolution of Indonesian Banking (LAPSPI). In this study, it was used descriptive empirical research with qualitative data analysis methods. The location of this research is the Alternative Institution of Dispute Resolution of Indonesian Banking (LAPSPI) and the Financial Services Authority (OJK). The results of this study explained that out of 134 registered disputes handled by LAPSPI, there were 35 disputes resolved through Mediation (dispute resolution was carried out in Jakarta, Ketapang, Padang, Pekanbaru, and Malang), 1 dispute was resolved through the Arbitration service, 6 disputes were still pending, 24 disputes were rejected because they did not meet the requirements, and 68 disputes were returned to the applicant to be resolved through the IDR process. From the above data it can be concluded that the existence and effectiveness of LAPSPI have not met expectations. There are still many requests that are rejected, indicating that there are many people who do not understand what is LAPSPI. Therefore it is the duty of LAPSPI to be able to introduce themselves to the community. In addition, in this case LAPSPI also needs to provide intense education and socialization to the community so that this institution can be better known by them.